Work against common myths to promote access, equity. Issue 2 (November 2016) - Hope, Joan
Abstract : COLUMBUS, Ohio — When Patricia McGuire became president of Trinity Washington University in 1989, the institution faced significant enrollment and economic challenges. Following a transformation that led to a diverse student body, Trinity thrives.